2006
DOI: 10.1503/cmaj.051707
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of driving cessation in mild-to-moderate dementia

Abstract: A landmark study of the epidemiology of dementia, the Canadian Study on Health and Aging (CSHA) determined that in 1992, some 316 500 Canadians over the age of 65 years (1 in 13) had dementia, with the risk of the disease doubling for every 5 years of age after 65.1,2 With the increasing mean age of our population, it is estimated that 500 000 Canadians will have dementia by 2021, and 750 000 by 2031.3 Although incidents involving drivers affected by dementia frequently make the headlines in the lay press, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 21 publications
4
61
1
15
Order By: Relevance
“…In patients with mild to moderate dementia (mean MMSE ϭ 21.9), a Class II study 31 reported that agitation and aggression were predictive of a refusal to discontinue driving (hazard ratio for driving cessation ϭ 0.54, 95% CI 0.32-0.90). In a Class III study of all-aged drivers (downgraded one evidence class), 32 deliberate violations of driving laws, across all ages, correlated with future crashes (␤ ϭ Ϫ0.12, p Ͻ 0.001).…”
Section: Reduced Mileage and Situational Avoidance Evidence From Stumentioning
confidence: 99%
“…In patients with mild to moderate dementia (mean MMSE ϭ 21.9), a Class II study 31 reported that agitation and aggression were predictive of a refusal to discontinue driving (hazard ratio for driving cessation ϭ 0.54, 95% CI 0.32-0.90). In a Class III study of all-aged drivers (downgraded one evidence class), 32 deliberate violations of driving laws, across all ages, correlated with future crashes (␤ ϭ Ϫ0.12, p Ͻ 0.001).…”
Section: Reduced Mileage and Situational Avoidance Evidence From Stumentioning
confidence: 99%
“…Insight into one's driving capabilities may play a role in the decision making regarding driving cessation or restriction. Although prior studies have shown that driver perceptions are related to self-regulatory practices in healthy older drivers Myers et al, 2011), those with cognitive impairment may lack the capacity to recognize their driving limitations and restrict their driving practices to compensate appropriately (Herrmann et al, 2006;Rapoport et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of studies suggest that individuals with moderate to severe dementia are unable to drive, there is no clear definition regarding the onset of dementia [62][63][64], relatively little is known about the driving performance of senior drivers with MCI [51,65], few studies demonstrate the relationship between MCI and driving performance [65][66][67][68][69][70][71][72][73], and there is no full consensus on the measurement of impairment in driving in seniors with MCI or whether they consequently have a higher risk of accidents compared to healthy people of the same age [51,64]. The available research from driving simulators and road studies suggests that drivers with MCI have prominent difficulties with navigation and decisions.…”
Section: Cognitive Ageing Aspects: Experience and Car Drivingmentioning
confidence: 99%